Geochemical features of the accumulation and migration of heavy metals in the peats of the Lviv region - Yakovenko, Myroslava; Khokha, Yurii; Lyubchak, Oleksandr (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Problem formulation. Study and interpretation of geochemical characteristic, component composition, content of macro- and microelements in peat has both a general scientific fundamental character and an applied one. Its results used for various purposes: quality assessment of peat, determination of the possibility of their use in industry etc. The article is devoted to study of the elements and microelements distribution in the peat of the Lviv region. The study of peatlands in western Ukraine and their component composition carried out only during geological exploration aimed at assessing the regions potential to produce own peat fertilizers or fuel. Article purpose. The aim of the work is to present an extended geochemical characteristic of Lviv’s region peats, to determine peats typical microelement composition and geochemical specialization, to establish regional regularities of distribution and accumulation of elements using methods of mathematical and statistical analysis, and to study the factors controlling the content, distribution and genesis of microelements in the region peatlands. Object, subject, factual material and research methods. The object of research is peat and its ash from peatlands of the Lviv region. The subject of research is geochemical characteristic of this peat, regional patterns of distribution and accumulation of chemical elements, components and geological and geochemical indicators in peats. The ashes of 248 peat samples taken in 110 representative areas were analyzed by spectral semi-quantitative analysis for the content of 21 chemical elements and other geochemical characteristics of peat (pH, ash content, etc.). Discussion. An integrated approach to the study of the geochemical characteristics of peat made it possible to identify the spatial geochemical features of peats in the territory of the Lviv region, to determine their typical microelements composition, to establish regional regularities of their distribution and accumulation (changes) - significant unevenness of the concentration of microelements by area of distribution, high indicators of the content of Mo, Yt, Sr, Co, Ag, Ba, Be, Pb in relation to the clarks of the lithosphere, soils, and plants. According to the results of correlation, factor and cluster analyzes, the following typomorphic geochemical associations of peats of the Lviv region can be distinguished: Ti-Ga-Cu-Y-Pb-Sc-V-Yb-Be is associated with the features of natural soil-forming processes of geochemical landscapes; Ni-Mo-Zn is possibly of technogenic origin and is associated with the accumulation of heavy metals in soils due to the development of mineral deposits. Conclusion. The analysis of the spatial distribution, mathematical and statistical processing of the geochemical characteristics and the composition and given varimax factor features and other integral and single-component parameters of peats described in the study indicates their satisfactory condition and can be to conclude that there is no regional pollution of peats in the Lviv region with heavy metals (except for Mo) or that the regional impact of such pollution is completely insignificant.